Effect of home processing methods on the levels of heavy metal contaminants in four food crops grown in and around two mining towns in Ghana - Rebecca Adjei-Mensah (Elsevier, 2021)
Unregulated small-scale mining activities, by young untrained men using some poisonous chemicals, occur in several agricultural forest belts in Ghana. These activities contaminate water bodies in these areas, which happen to be the main farming sites where food crops are intensively cultivated. The presence of these heavy metal contaminants in popular food staples is therefore worrying because of its adverse health implications. Previous studies have shown that processing is able to decrease the concentrations of heavy metals in foods. This study investigated the effectiveness of home processing methods (boiling, frying and roasting) in significantly reducing the levels of heavy metal contaminants in food crops grown in and around two main mining centers in Ghana. The heavy metals contaminants analyzed for, were Arsenic (As), Cadmium, (Cd), lead (Pb), Manganese (Mn), and Mercury (Hg), determined using atomic absorption spectrometry (AAS) and inductively-coupled plasma mass spectrometry (ICP-MS). From the data, the average daily intakes of the heavy metals and the associated long-term health risks to consumers were assessed. Unprocessed samples from Akwatia had higher levels of contaminants than those from Obuasi. Levels of Mn, Pb and As recorded in all unprocessed samples were higher compared to WHO permissible limits in foods. The levels showed a decreasing trend in the processed samples; with the lowest As and Pb content recorded after frying and boiling. The study showed that roasting allowed for the least reduction in the heavy metal contaminations in the four food crops. The levels of Cd in both processed and unprocessed samples were within safe WHO specifications. Except for Pb in unprocessed cassava, boiled cassava and unprocessed plantain and Hg (unprocessed yam and roasted yam), the hazard indices of all metals in all food crops were less than one and posed no risk to consumers. The study therefore reveals that the normal home processing methods are able to reduce the levels of heavy metal contaminants found in cassava, cocoyam, plantain and yam considerably.